The effect of midwife-based listening visit on stress, anxiety, and depression among mothers of premature infants in the neonatal intensive care unit: Randomized clinical trial study - Najmeh Ebadi; Mahtab Attarha; Mustafa Nokani (Wolters Kluwer Medknow Publications, 2022)
Background: Mothers of infants hospitalized in the Neonatal Intensive Care Unit (NICU) may experience a variety of psychological problems such as anxiety, depression, and stress. This study investigated the effect of midwife-based Listening Visit (LV) on stress, anxiety, and depression among mothers of premature infants in the NICU. Materials and Methods: This randomized clinical trial study was performed on 60 mothers of premature neonates who were admitted to the NICU of Taleghani Maternity Hospital between February and April 2018 in Arak, Iran. They were selected through simple random sampling. For the intervention group (n = 30), six counseling sessions were held twice a week. The control group (n = 30) did not receive any intervention. The mean values of stress, anxiety, and depression were measured before and 4 and 8 weeks after the intervention. Data were gathered using the Depression, Anxiety, Stress Scale-21 (DASS-21). The t-test and Chi-square test were used to analyze the data. Results: The mean scores of anxiety (F (2, 98) = 19.92, p < 0.001), stress (F (2, 98) = 43.94, p< 0.001), and depression (F (2, 98) = 42.95, p< 0.001) significantly reduced after 4 and 8 weeks of intervention in the LV group. Conclusions: LVs delivered by midwives can be effective in improving anxiety, stress, and depression in mothers of preterm infants in the NICU. Implementation of LV in the NICU resolves a recognized need and highlights the importance of psychological screening, and monitoring and support services for these mothers.